THE ROLE OF NATIONAL HOSPITALS IN THE DISASTER MEDICINE, ESPECIALLY IN A LARGE-SCALE TRAFFIC ACCIDENT - NABETANI, Jyuukichi; YOSHIDA, Kazuya; YAMASHITA, Akemi; MURAYAMA, Yoshio; KOSUGA, Hirofumi; OHTA, Keiko; YAMADA, Masahiro (Japanese Journal of National Medical Services, 1995)
While there is a possibility of large-scale disasters occurring anywhere in Japan, the area around our hospital is a key points of traffic and it is highly possible that major traffic accidents occur there. Since the Shigaragi Railway Accident in 1992, we have studied measures to cope with a large-scale disaster, have made arrangements to provide various emergency materials and have worked out with relevant manuals. On the basis of these measures, we carried out a simulation with the disasters at the Shigaragi railway, Osaka Newtram and Nagoya Airport taken as examples. If preparations are made in advance, our hospital alone could possibly cope with even considerably h rge-scale disasters. In large-scale disasters, however, there is a limit as to what a single hospital can do so that nation-wide assistance and co-operation of national hospitals are indispensable. Issues such as giving correct informations on the disaster, integrating two or more agencies, dispatching relief squads, storing materials for emergency and securing vacant beds were suggested. Comprehensive training regarding these issues was thought to be crucial.